Extração de biocorante de líquen visando a dopagem de matriz híbrida sílica/orgânico para aplicações ópticas - Marques, Laura Cristina Boschi (2024)
The obtaining of products that do not harm the environment is of utmost importance. The dye industry, specifically the textile industry, is one of the largest sources of contaminants, causing serious environmental issues such as contamination of aquatic ecosystems, soil, among others. In an effort to mitigate these problems, the use of natural sources has gained attention from the scientific community, offering a sustainable alternative to synthetic dyes. Alongside this, the use of glassy materials for various optical purposes is also significant, although depending on the dopant added, they can exhibit toxicity levels and disposal issues after their useful life.In this context, the objective of the present study was to evaluate the effects of doping with natural lichen dye in a silica/organic hybrid matrix, in order to understand how such a dye interacts with the matrix structure. To achieve this, the dye was obtained through acid/base extraction using NH4OH as a solvent to remove lichen acids from the raw material. Subsequently, six samples were synthesized via Sol-Gel synthesis using GPTS/TEOS as precursor agents, with five of them doped with different concentrations of the dye and one without doping. Once prepared, the samples were characterized using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Thermal Analyses (TGA/DSC).From the XRD results, it was observed that all samples maintained an amorphous silicon structure, while FTIR results identified vibration modes corresponding to both organic and inorganic phases, confirming the formation of a hybrid matrix. Both results also indicated that the doping process did not significantly alter the structural part of the matrix. TGA/DSC analyses revealed a trend of increased thermal stability for samples with higher dopant concentrations. Spectroscopic properties in the UV-VIS region of this system were also characterized. The studied dye exhibited two characteristic absorption bands, between 200-300nm and 450-600nm. The absorption spectra of the GPTS/TEOS samples showed that the doping process imparted the matrix with the same absorption profile as the dye.Furthermore, the emission properties of the doped system were characterized. Under excitation at 532nm, the samples showed an intense emission band in the red region, centered at ~620nm. Under excitation at 405nm, these samples exhibited broad emission covering almost the entire visible spectrum. Additionally, under UV excitation, increasing the dopant concentration resulted in a better balance in the RGB ratio, leading to a reduction in color temperature and high values of color rendering index (CRI) for the emitted light. These results indicate that the GPTS/TEOS hybrid matrix doped with lichen-extracted dye possesses promising properties for applications in red-emitting devices when excited at 532nm, and high-quality white light emission when excited in the UV range.